2007
DOI: 10.17221/2088-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and costs of the mechanised cut-to-length wood harvesting system in clear-felling operations

Abstract: A study of labour productivity was conducted in fully mechanised harvesting technologies. The study revealed that the productivity of harvesters was particularly affected by the average tree volume of the felled trees, and the productivity of forwarders was affected mainly by two factors -haulage distance and machine payload. Dependences of other factors such as natural and site conditions, technical parameters and skills of operators could not be demonstrated. Regression equations of dependences were created … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
66
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 2 publications
(1 reference statement)
9
66
1
4
Order By: Relevance
“…When comparing the cutting productivity of normal standing trees in this study to the cutting productivity of Norway spruce in the study by Nurminen et al [76], it is noted that the cutting productivity in this study was higher when the stem size of removal was <0.76 m 3 (Figure 8), and the opposite was found with larger spruce stems. The cutting productivities reported by Brunberg [81], Jiroušek et al [82] and Eriksson and Lindroos [62] are also quite close to the average cutting productivity level in the normal clear cuts in this study (Figure 8).…”
Section: Evaluation Of the Main Findingssupporting
confidence: 86%
See 1 more Smart Citation
“…When comparing the cutting productivity of normal standing trees in this study to the cutting productivity of Norway spruce in the study by Nurminen et al [76], it is noted that the cutting productivity in this study was higher when the stem size of removal was <0.76 m 3 (Figure 8), and the opposite was found with larger spruce stems. The cutting productivities reported by Brunberg [81], Jiroušek et al [82] and Eriksson and Lindroos [62] are also quite close to the average cutting productivity level in the normal clear cuts in this study (Figure 8).…”
Section: Evaluation Of the Main Findingssupporting
confidence: 86%
“…The cutting productivities reported by Brunberg [81], Jiroušek et al [82] and Eriksson and Lindroos [62] are also quite close to the average cutting productivity level in the normal clear cuts in this study (Figure 8). Hence, on the basis of the results of this study, it can be concluded that a big leap has not necessarily been taken in the development of forest machine technology during the last ten years.…”
Section: Evaluation Of the Main Findingssupporting
confidence: 86%
“…Since the exponent is larger than 1, the curve bends upwards and describes the typical phenomenon of increasing returns, which in this specific case has been interpreted as the scale effect of engine power. Conversely, curves relating productivity to piece size use exponents smaller than 1 and bend downwards, indicating diminishing returns as piece size increases [26]. That is important to notice, because it demonstrates that productivity is directly proportional to both engine power and piece size, and yet investments in engine power are more productive, as returns are higher and may easily offset limitations in piece size.…”
Section: Robust Productivity Modelmentioning
confidence: 99%
“…When buying a whole harvester or a harvester head for the available base machine (the excavator, for instance), the technical features of the equipment should fit operational conditions to avoid unnecessary impairment of its effectiveness. Many developments have been made towards improvement of fully mechanized CTL in the field of harvester productivity and costs [1,[7][8][9][10][11][12], which are dependent upon the silvicultural system, operational phase, ambient temperature, outcome product, stand factors, operator factors and machine factors, terrain and climatic conditions, as well as growing stock per hectare according to a region [13].…”
Section: Introductionmentioning
confidence: 99%